catena-Poly[[triphenyltin(IV)]-mu(2)-[3-(cyclohexylcarbamoy)propan oato-kappa O-2(1):O-3]] - Shams-ul-Islam, S.; Bhatti, M.H.; Imtiaz-ud-Din, A.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The Sn atom in the polymeric title compound, [Sn(C6H5)(3)-(C10H16NO3)](n), is five-coordinated within a trans-C3O2 donor set that defines an approximate trigonal-bipyramidal geometry. The carboxylate ligand is monodentate and the amide O atom bridges a symmetry-related Sn atom, generating a chain along [010] with a linear topology. An intramolecular carboxylate-carbonyl N-H center dot center dot center dot O hydrogen bond is responsible for the curved conformation within the carboxylate ligand.